2018
DOI: 10.3390/en11071663
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chelating Agent-Based Polymeric Gel System for Hydraulic Fracturing

Abstract: Hydraulic Fracturing is considered to be one of the most important stimulation methods. Hydraulic Fracturing is carried out by inducing fractures in the formation to create conductive pathways for the flow of hydrocarbon. The pathways are kept open either by using proppant or by etching the fracture surface using acids. A typical fracturing fluid usually consists of a gelling agent (polymers), cross-linkers, buffers, clay stabilizers, gel stabilizers, biocide, surfactants, and breakers mixed with fresh water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…This is because seawater contains sulfate ions, among others, which might react with the formation divalent ions, such as calcium, to form calcium sulfate, which is known for plugging the pore throats and reduces permeability . Recently, many studies focused on developing a fracture fluid system that is compatible with produced water or seawater. , Kamal et al proposed using GLDA for acid and propped fracturing operations. The study suggested that GLDA could replace many fracturing fluid additives, such as clay stabilizers, biocides, cross-linkers, and breakers.…”
Section: Chelating Agents As Hydraulic Fracturing Fluid Additivesmentioning
confidence: 99%
“…This is because seawater contains sulfate ions, among others, which might react with the formation divalent ions, such as calcium, to form calcium sulfate, which is known for plugging the pore throats and reduces permeability . Recently, many studies focused on developing a fracture fluid system that is compatible with produced water or seawater. , Kamal et al proposed using GLDA for acid and propped fracturing operations. The study suggested that GLDA could replace many fracturing fluid additives, such as clay stabilizers, biocides, cross-linkers, and breakers.…”
Section: Chelating Agents As Hydraulic Fracturing Fluid Additivesmentioning
confidence: 99%
“…Kamal et al [16] developed a new smart fracturing fluid system mainly consisting of a water-soluble polymer and chelating agent, which can be either used for proppant fracturing (high pH) or acid fracturing (low pH) operations in tight as well as conventional formations. The optimal conditions and concentration of this fracturing fluid system were determined by performing thermal stability, rheology, Fourier transform infrared spectroscopy, and core flooding experiments.…”
Section: Overview Of Work Presented In This Special Issuementioning
confidence: 99%
“…Several chelating agents are known for their compatibility in stimulation fluid to capture ions; however, their stability under harsh conditions and impact on the formation is crucial. In our previous work, we found that polymer dissolved in seawater and chelating agent proved extremely effective in leaving minimal formation damage and exhibiting favorable characteristics in fracking fluids, such as requiring no breaker and showing excellent stability under high temperatures [13,20]. This paper will instead focus on the produced water as means for recycling, which, as found in the literature above, can have a distinctively different composition than seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work conducted with EDTA and DTPA chelating agents showed that both chelates do not have the capability of breaking the polymers because they formed very stable components. GLDA has the ability to thicken the polymer viscosity, and at the same time, it can break the polymer backbone based on its ph and concentration at different temperatures [13]. DTPA and EDTA chelating agents are very common in oil and gas industry applications, but they have limited solubility at low ph values and cannot handle high salinity water such as produced water [14].…”
Section: Introductionmentioning
confidence: 99%